Day 2 Tue, May 03, 2016 2016
DOI: 10.4043/26961-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Seismic Response of Offshore Slopes Using 1, 2, or 3 Ground Motion Components

Abstract: Offshore landslides pose a major threat to subsea facilities, and one of the main triggering factors of offshore landslides is strong earthquakes. The state of the practice models offshore slope stability during strong shaking using one horizontal component of a selected representative ground motion. However, slopes and earthquakes are three-dimensional phenomena. Therefore, to provide much needed guidance in this area, this study performed 27 three-dimensional seismic slope stability analyses in a finite elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The modelling attempt of this study included only one dimension of earthquake shaking, whereas seismic waves in reality affect the sedimentary sequence in three dimensions (Carlton and Kaynia, 2016). The lower earthquake frequencies are closer to the resonance frequency of sediment layers and attenuate more slowly within the sediments.…”
Section: Quantification Of Trigger Mechanisms Of the Tampen Slidementioning
confidence: 99%
“…The modelling attempt of this study included only one dimension of earthquake shaking, whereas seismic waves in reality affect the sedimentary sequence in three dimensions (Carlton and Kaynia, 2016). The lower earthquake frequencies are closer to the resonance frequency of sediment layers and attenuate more slowly within the sediments.…”
Section: Quantification Of Trigger Mechanisms Of the Tampen Slidementioning
confidence: 99%
“…To avoid wave reflections along the model boundaries, tied boundary conditions (Zienkiewicz et al, 1989) were defined in both horizontal directions at each elevation of the mesh to constrain the model to deform as a shear beam and achieve a free-field condition. The approach of using of 3-D brick elements in OpenSees has been applied verified against models implemented in PLAXIS 3D and FLAC 3D (Carlton et al, 2020) and PLAXIS 2D (Løkke and Carlton, 2022) in the simulation of multidirectional shaking in offshore slopes. Soriano (2021) simulated by means of 3-D brick element columns the experimental response of instrumented gentle slopes in soft clay and tested in a geotechnical centrifuge with good agreement between the experimental and numerical results in terms of accelerations throughout the slopes and seismic displacements.…”
Section: Numerical Model Parametersmentioning
confidence: 99%
“…For the 100 m deep soil profile, multi-directional shaking predicted 30% increase in excess pore pressure at large depths, which reduced to 10% at the soil surface, whereas the 20 m deep soil profile predicted an increase in excess pore pressure between 20% and 40%. Carlton and Kaynia (2016) conducted a number of numerical simulations in which 3-D slopes of NC clay with simple Mohr-Coulomb failure criterion were subjected to one-component and 3-component earthquake excitations. Through a number of case studies, they observed that inclusion of the earthquake component perpendicular to the slope direction increases the permanent downslope displacements and shear strains in the slope by 25%-50% and by 10%-50%, respectively.…”
Section: Multi-directional Shakingmentioning
confidence: 99%
“…Response of slope for 3-component (above) vs one-component (below) earthquake (adapted fromCarlton & Kaynia, 2016) …”
mentioning
confidence: 99%